On the numerical solutions of some fractional ordinary differential equations by fractional Adams-Bashforth-Moulton method - Baskonus, Haci Mehmet; Bulut, Hasan (Sciendo, 2015)
In this paper, we apply the Fractional Adams-Bashforth-Moulton Method for obtaining the numerical solutions of some linear and nonlinear fractional ordinary differential equations. Then, we construct a table including numerical results for both fractional differential equations. Then, we draw two dimensional surfaces of numerical solutions and analytical solutions by considering the suitable values of parameters. Finally, we use the L-2 nodal norm and L-infinity maximum nodal norm to evaluate the accuracy of method used in this paper.
Keywords: Fractional Adams-Bashforth-Moulton method; Fractional calculus; Fractional nonlinear ordinary differential equation